Intussusception of the bowel in adult women due to bulky inflammatory fibroid polyp treated in emergency. A case report - Rollo, Alessio; Lugani, Pietro; Casali, Lorenzo; Montali, Filippo; Scaramuzza, Lucia; Gandolfi, Giorgia; Thai, Elena; Costi, Renato (Acta Biomedica Atenei Parmensis, 2022)
Introduction: Intussusception represents a rare form of bowel obstruction in the adult, which is defined as the telescoping of a proximal segment of the gastrointestinal tract into the lumen of the adjacent distal segment of the GI tract Case Report: We report the case of a 50-year-old woman was admitted in our hospital with acute bowel obstruction. CT showed intestinal occlusion secondary to intussusception. the patient underwent emergency surgery. Surgery confirmed intussusception at the level of the distal ileum (about 30 cm from the ileocecal valve) due to a 3-4 oval mass of hard consistency that appeared to be suspicious for GIST. Was performed a resection of the ileal segment involved associated with oncologically radical lymphadenectomy. The histological examination reported benign ileal mesenchymal neoformation compatible with inflammatory fibroid polyp. Patient had a regular course Discussion: In adults, 90% of invaginations manifest as a result of an organic lesion caused by benign or malignant tumors. The clinical presentation in adults is generally chronic or nonspecific. The emergence of acute symptoms due to complete intestinal obstruction occours in fewer than 20% of patients. Abdominal computed tomography (CT) is the most sensitive radiologic method to confirm intussusception. As many cases are secondary to organic pathologies with malignant potential, surgical resection of the affected bowel segment with oncological procedures is the primary method of treatment Conclusion: Due to the fact that adult intussusception is often frequently associated with organic lesions, surgical intervention is necessary. Treatment usually requires formal resection of the involved bowel segment. (www.actabiomedica.it)